War in Afghanistan and Iraq : the daily life of the men and women serving in Afghanistan and Iraq - Souter, Janet, 1940-; Souter, Gerry (London : Carlton Books, 2011)
Text, photographs, maps, and illustrations answer questions about the wars in Afghanistan and Iraq and describe the work and lives of soldiers.
Kirkus Review, September 2011
Includes index.
6.4
3-6
Keywords: Afghan War, 2001- -- Juvenile literature; Iraq War, 2003-2011 -- Juvenile literature; Soldiers -- United States -- Juvenile literature; Afghan War, 2001-; Iraq War, 2003-2011.; Soldiers; Afghan War, 2001-; Iraq War, 2003-2011.; Soldiers